2021
DOI: 10.3390/ijerph18052449
|View full text |Cite
|
Sign up to set email alerts
|

Are Countries of the Eastern Mediterranean Region on Track towards Meeting the World Health Assembly Target for Anemia? A Review of Evidence

Abstract: Anemia is a multifactorial condition, with a complex etiology that involves nutritional and non-nutritional factors. The misconception that iron deficiency is equivalent to anemia may mask the need to address other potential causative factors. This review paper aims to (1) assess the burden of anemia vs. iron deficiency anemia (IDA) amongst women of reproductive age (WRA), pregnant women (PW), and children under five years old (underfive children, U5C) in the Eastern Mediterranean region (EMR); (2) evaluate tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 69 publications
0
24
0
1
Order By: Relevance
“…In 2008, the national higher committee of nutrition in Jordan modified this process by maintaining only the first dose of 100,000 IU. Then in 2012, in response to the increased prevalence of vitamin A deficiency, the national higher committee of nutrition retained the second dose of 200,000 IU vitamin A and requested to continuously monitor and evaluate the distribution of vitamin A capsules and documents provided in the national vaccines card [ 28 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2008, the national higher committee of nutrition in Jordan modified this process by maintaining only the first dose of 100,000 IU. Then in 2012, in response to the increased prevalence of vitamin A deficiency, the national higher committee of nutrition retained the second dose of 200,000 IU vitamin A and requested to continuously monitor and evaluate the distribution of vitamin A capsules and documents provided in the national vaccines card [ 28 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…In children aged 6–59 months old, the prevalence in 2017–2018 was classified as a moderate public health problem [ 26 ]. Among children aged 12–59 months, the rates of anemia and iron deficiency in 2010 were categorized as mild public health concerns, while that of iron deficiency anemia was considered normal [ 26 , 27 , 28 , 46 ]. Over time, the rates of anemia did not show significant progress, whereas a decreasing trend in the prevalence of iron deficiency was observed, which may be attributed to the implementation of the national wheat flour fortification with multiple micronutrients including iron [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, we found an overall prevalence of 49.5 % in pregnant women. It's a way leading towards achieving WHO Sustainable Development Goals (SDG) 2025 for the health of pregnant women [17] as according to Ayoub et al, Pakistan is on the right track to achieve these goals [19].…”
Section: Discussionmentioning
confidence: 99%
“…The National Nutritional Survey (NNS) 2018 showed that 56.6% of adolescent girls and 42.7% of women of reproductive age were to be anemic [16][17][18]. It is good that Pakistan is among the countries that are on the right track to get rid of anemia [19]. But still, a lot of work is to be done to eradicate it.…”
Section: Introductionmentioning
confidence: 99%